Current understanding of chemotherapy-induced peripheral neuropathy (literature review) - O. A. Tikhonova; D. S. Druzhinin; A. M. Tynterova; I. V. Reverchuk (Нервно-мышечные болезни)
This review focuses on chemotherapy-induced polyneuropathy, which is a fairly common side effect and affects not only the quality of life of patients with malignancies, but can also lead to a change in patient management tactics, namely dose modification, delay of drug administration to complete cessation of treatment, which threatens the life of the patient. Chemotherapy-induced polyneuropathy is based on different mechanisms of damaging effects depending on the type of cytotoxic agent. The most neurotoxic drugs are platinum drugs, taxanes, periwinkle alkaloids, bortezomib, and thalidomide. As a result of neurotoxic effects, damage occurs to thin and thick fibers of peripheral nerves. However, it is still a mystery why one patient develops manifestations of neurotoxicity and another does not. Therefore, the modern medical community is faced with the urgent question of further study of the mechanisms of development, risk factors, as well as the search for biomarkers and the development of prevention and treatment of chemotherapy-induced polyneuropathy. The results of studies on the mechanism of onset, clinic, diagnosis, prevention and treatment of chemotherapy-induced polyneuropathies are summarized.